Flame behaviors and overpressure characteristics of the unconfined acetylene-air deflagration. (1st May 2022) - Wang, Wentao; Cheng, Yangfan; Wang, Rui; Wang, Hao; Wang, Quan; Liu, Rong; Ma, Honghao
Abstract: Flame propagation behaviors and overpressure distributions of acetylene-air deflagrations were studied using latex balloons, and the combustion processes were also simulated by the Chemkin software. Experimental results showed that, as the equivalence ratio increased, the laminar flame speed raised at first and then declined, and its maximum value (1.36 m/s) was obtained with the equivalence ratio of 1.32. According to the sensitivity analysis of Chemkin software, H + O2 ↔O + OH and HCO + H↔CO + H2 were the typical reactions to promote and inhibit the laminar flame speed, respectively. The radical H played an important role in increasing the chemical reaction rate and its concentration in the flame could reflect the magnitude of laminar flame speed. When the oxygen was insufficient, the sensitivity coefficients of the radical reactions consuming O and OH radicals declined, while those of the radical reactions generating O and OH increased gradually. Deflagration overpressure of acetylene-air mixtures with different equivalence ratios were measured, and the pressure attenuation of the fuel-rich mixture was lower than that of fuel-lean one. In addition, the effects of static placing time on the combustion characteristics of hybrid acetylene/air were studied. Highlights: Freely propagated flame of C2 H2 -air was studied by the latex balloon method. Combustion species of C2 H2 -air were analyzed in details with Chemkin software. Overpressure characteristics of C2 H2 -air with various concentrations were discussed. Influence of static placing time on C2 H2 -air deflagration parameters were studied.